Lymphatic vessels in vascularized human corneas: immunohistochemical investigation using LYVE-1 and podoplanin. - Cursiefen, C; Schlötzer-Schrehardt, U; Küchle, M; Sorokin, L; Breiteneder-Geleff, S; Alitalo, K; Jackson, D (2002)
PURPOSE: To determine whether lymphatic vessels exist in vascularized human corneas, by using immunohistochemistry with novel markers for lymphatic endothelium. METHODS: Human corneas exhibiting neovascularization secondary to keratitis, transplant rejection, trauma, and limbal insufficiency (n = 21) were assessed for lymphatic vessel content by conventional transmission electron microscopy and by immunostaining and immunoelectron microscopy with antibodies specific for the lymphatic endothelial markers, lymphatic vessel endothelial hyaluronan receptor (LYVE-1) and the 38-kDa integral membrane glycoprotein podoplanin. In addition, corneas were stained for the lymphangiogenic growth factor VEGF-C, and its receptor VEGFR3 by immunohistochemistry and in situ RNA hybridization, respectively. RESULTS: Thin-walled, erythrocyte-free vessels staining with lymphatic markers (LYVE-1 and podoplanin) were found to constitute 8% of all vessels, to be more common in the early course of neovascularization, to be always associated with blood vessels and stromal inflammatory cells, and to correlate significantly with the degree of corneal hemangiogenesis (r = 0.6; P = 0.005). VEGF-C, VEGFR3, podoplanin, and LYVE-1 colocalized on the endothelial lining of lymphatic vessels. With immunogold labeling, LYVE-1 and podoplanin antigen were found on endothelial cells lining vessels with ultrastructural features of lymph vessels. CONCLUSIONS: Immunohistochemistry with novel lymph-endothelium markers and ultrastructural analyses indicate the existence of lymphatic vessels in vascularized human corneas. Human corneal lymphangiogenesis appears to be correlated with the degree of corneal hemangiogenesis and may at least partially be mediated by VEGF-C and its receptor VEGFR3.